2010
DOI: 10.1007/s10806-010-9237-7
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Salmon Feed: A Deliberative Assessment of Several Alternative Feed Resources

Abstract: The future of salmon aquaculture depends on the adoption of alternative feed resources in order to reduce the need for fish meal and fish oil. This may include resources such as species from lower trophic levels, by-products and by-catch from fisheries and aquaculture, animal by-products, plants, genetically modified (GM) plants, nutritionally enhanced GM plants and products from microorganisms and GM microorganisms. Here, we report on a deliberative assessment of these alternative feed resources, involving 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…This technique not only enables a clear picture to be developed about how different stakeholders view the available alternatives and how they weight different evaluative criteria, it also captures how they see the uncertainties involved and how these uncertainties affect their preferences and decision making. This allows biotechnologies to be compared with a range of other technologies for their potential to address the problem at hand against diverse evaluative criteria [ 23 ].…”
Section: Five Essential Features Of Responsible Governance Of Agriculmentioning
confidence: 99%
“…This technique not only enables a clear picture to be developed about how different stakeholders view the available alternatives and how they weight different evaluative criteria, it also captures how they see the uncertainties involved and how these uncertainties affect their preferences and decision making. This allows biotechnologies to be compared with a range of other technologies for their potential to address the problem at hand against diverse evaluative criteria [ 23 ].…”
Section: Five Essential Features Of Responsible Governance Of Agriculmentioning
confidence: 99%
“…In this regard, formulation of suitable diets for farmed salmon requires inclusion of fish meal and fish oil in appropriate quantities, to give the final product the required nutritional quality and composition. Usually, formulated diets for salmon constitute 40-60% fish meal and 20-30% fish oil, sourced mainly from marine anchovies, mackerel, pilchards, herring and blue whiting [45]. These marine fish species are often targeted as sources of fish meal and fish oil for salmon feed production because they provide appropriate nutrients for carnivorous fish species and offer appropriate amounts of polyunsaturated fatty acids (omega 3), in the fillets of the salmon, which is beneficial for human health.…”
Section: High Cost Of Feeds For Salmon Productionmentioning
confidence: 99%
“…In one study carried out by Kvakkestad et al (2007) it was found that that different scientists, depending on scientific discipline (ecology, molecular biology, plant breeding), source of funding (public or industry) or whether they worked within industry, government or academia, interpreted data differently in situations characterised with uncertainty, and thus expressed a diversity of opinions about the risks arising from GM crops. In a recent study by Gillund and Myhr (2010) perspectives on alternative feed resources for salmon were identified among stakeholders in Norwegian aquaculture. In this study the sustainability of plant production in industrial agriculture, and particularly the cultivation of GM plants, was contested among the participants.…”
Section: Researchers Opinions and Attitudes To New Biotechnologiesmentioning
confidence: 99%